Coriolanus - Shakespeare, William; Edited by Mowat, Barbara A.; Werstine, Paul (New York Simon & Schuster Paperbacks, 2009)
Critical and historical notes accompany Shakespeare's play about the life of an ambitious military leader.
English Drama.
Keywords: Coriolanus, Cnaeus Marcius -- Rome (Empire) -- Generals